Injury Activates a Dynamic Cytoprotective Network to Confer Stress Resilience and Drive Repair. - Weavers, H.; Wood, W.; Martin, P. (Current Biology, 2019)
In healthy individuals, injured tissues rapidly repair themselves following damage. Within a healing skin wound, recruited inflammatory cells release a multitude of bacteriocidal factors, including reactive oxygen species (ROS), to eliminate invading pathogens. Paradoxically, while these highly reactive ROS confer resistance to infection, they are also toxic to host tissues and may ultimately delay repair. Repairing tissues have therefore evolved powerful cytoprotective "resilience" machinery to protect against and tolerate this collateral damage. Here, we use in vivo time-lapse imaging and genetic manipulation in Drosophila to dissect the molecular and cellular mechanisms that drive tissue resilience to wound-induced stress. We identify a dynamic, cross-regulatory network of stress-activated cytoprotective pathways, linking calcium, JNK, Nrf2, and Gadd45, that act to both "shield" tissues from oxidative damage and promote efficient damage repair. Ectopic activation of these pathways confers stress protection to naive tissue, while their inhibition leads to marked delays in wound closure. Strikingly, the induction of cytoprotection is tightly linked to the pathways that initiate the inflammatory response, suggesting evolution of a fail-safe mechanism for tissue protection each time inflammation is triggered. A better understanding of these resilience mechanisms-their identities and precise spatiotemporal regulation-is of major clinical importance for development of therapeutic interventions for all pathologies linked to oxidative stress, including debilitating chronic non-healing wounds.